THE WORDPLAY OF ‘THE BIG BANG THEORY’ MOVIE SUBTITLE - Isnu Maharani, Sang Ayu (Lingual Journal of Language and Culture, 2016)
This study aims to describe the type of wordplay in the subtitle of the movie entitled ‘The Big Bang Theory’ and also to describe the technique applied in translating the wordplay. This study is a descriptive qualitative and library study. The data was collected through observation and note taking techniques. The framework of this study is Delabatista (1993) concerning with types of wordplay translation and Humanika (2012) about the techniques to translate the wordplay. This study found that there are three types of wordplay; they are the phonological structure (homonymy and homophony), the lexical development (idiom) and the syntactic structure. The techniques of translating wordplay found consist of literal translation, loan translation, situational translation and no translation.
Keywords: Wordplay, translation, movie subtitle, ‘The Big Bang Theory’